Characterization of physicochemical traits, total carotenoids, volatile components, and orthonasal aroma profiles of new Okinawan pineapple (Ananas comosus) breeding lines - Asikin, Yonathan; Kudaka, Tomomasa; Maekawa, Ryota; Kobayashi, Takuya; Takeuchi, Makoto; Horiuchi, Masahiro; Wada, Koji (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2024)
Pineapple is an important representative fruit of Okinawa Prefecture, Japan. The fruits of the five new breeding lines (“Okinawa No. 22,” “Okinawa No. 25,” “Okinawa No. 26,” “Okinawa No. 27,” and “Okinawa No. 28”) were evaluated for physicochemical traits, total carotenoids, volatile components, and orthonasal aroma profiles. The fruits had comparable weight, total soluble solids, and titratable acidity but displayed different color space b* values (yellow index). This yellow indicator was positively associated with total carotenoid content, with the “Okinawa No. 26” line having the most (8.74 mg/kg). The amount and composition of volatile components and, consequently, aroma-active compounds varied between fruits. The “Okinawa No. 28” line contained the most active-aroma compound methyl 2-methylbutanoate (odor activity value = 297.78). Except for “Okinawa No. 25,” the lines were associated with pleasant orthonasal aromas, such as fruity, sweet, coconut-like, and peach-like, indicating their potential use in fresh or processed foods.